Role of Haemophilus influenzae in Formation of Infectious Diseases in Children - G.O. Lezhenko; O.Ye. Pashkova; L.I. Pantyushenko (Zaslavsky O.Yu., 2013)
The paper contains an analysis and synthesis of current views on the role of Haemophilus influenzae in the formation of infectious diseases in children. Own experience in determining the incidence of Haemophilus influenzae in respiratory pathology in children and determining the sensitivity and resistance of this pathogen to antibiotics are demonstrated. Expediency of using II-III generation cephalosporins in the treatment of infections caused by Haemophilus influenzae in children are substantiated.